Colegio San Felipe (2017)
"The San Felipe School is part of the emerging renovation that is located between 72nd Street and 80th Street on the western side of Caracas Avenue. It is the answer to the intrinsic need of children to learn. The experience understood as curiosity and research, will be the trigger for the project intentions, in this case, the architectural proposal must be seen as an answer to a problem not only spatial but pedagogical. The project, which is also born thanks to certain factors present in the place where it is implemented, seeks to be an educational center for the community in general by including the public space and not creating a barrier as normally exists in today's schools. It seeks to create a referent to improve the project system of schools in Bogota today." -- Tomado del Formato de Documento de Grado.